Prevalence and factors associated with resilience in Peruvian adolescent schoolchildren during the early post-pandemic context: a cross-sectional study - Valladares-Garrido, Mario J.; Cueva-Cañola, Luis E.; Grados-Espinoza, Pamela; Aguilar-Manay, Luz A.; Vásquez, Jassmin Santin; Valladares-Garrido, Danai; Pereira-Victorio, César J.; Vera-Ponce, Víctor J. (Frontiers in Psychiatry, 2025)
IntroductionResilience is a fundamental protective factor during adolescence, as it enables young people to cope with adversity and reduce the risk of mental health disorders. However, evidence on the prevalence and associated factors of resilience in adolescents remains limited in Latin America, particularly in school settings and the post-pandemic context. This study aimed to estimate the prevalence and associated factors of resilience among adolescents from five educational institutions in northern Peru.MethodsAn analytical cross-sectional study was conducted between September and December 2022, in the post-pandemic period, among 1,307 adolescents from five schools in the Lambayeque region, Peru. Data were collected using a self-administered digital questionnaire during school hours. Adolescents who regularly attended classes and completed all required items of the CD-RISC-10 scale were included. This secondary analysis of data used data from a primary study on adolescent mental health. The dependent variable was resilience, measured using the abbreviated CD-RISC-10 scale, and categorized as low (0–29 points) or high (≥30 points). Independent variables included sociodemographic, family, academic, and behavioral factors. Descriptive, bivariate, and multivariate analyses were conducted using generalized linear models (Poisson family) with robust variance, and prevalence ratios (PR) with 95% confidence intervals (95% CI) were reported.ResultsThe prevalence of high resilience was 17.3% (95% CI: 15.28–19.45). In multivariate analysis, frequent closeness with friends (PR: 1.93) and with relatives (PR: 1.47) were associated with higher resilience. Conversely, residing in urban areas (PR: 0.82), belonging to a non-Catholic religion (PR: 0.68), failing a course (PR: 0.78), cigarette use (PR: 0.46), and excessive internet use (>11 hours/day) (PR: 0.87) were associated with lower resilience.ConclusionsThese findings underscore the importance of social and family support in fostering resilience during adolescence during the early post-pandemic context. They also highlight the need for interventions to address modifiable risk factors, including smoking, excessive screen time, and poor academic performance. The implementation of mentoring and psychological counseling programs within schools, alongside strategies to promote resilience in educational and family environments, is strongly recommended.